FOUNDATION OF LEARNING RESOURCE CENTERS - Nur Ayu Winingsih; Rahmat olii (LPPM UNiversitas Bina Mandiri Gorontalo, 2024)
Education is one of the main pillars of a nation's development. To achieve this goal, a solid educational foundation is needed, and one of the key elements in the formal education system is a learning resource center. Formal learning resource centers have a strategic role in providing quality educational resources to support the learning process. Formal learning resource centers are a key element in the formal education ecosystem, and understanding the foundations of formal learning resource centers is a determining factor in responding to challenges and achieving quality education goals. In this context, the introduction has discussed the background, rationale, problems, research objectives and benefits of the research. The Learning Resource Center (PSB) in the context of formal education is not just a book warehouse; it involves a strong foundation for realizing quality education. The main goal of PSB is to achieve educational goals by providing resources that support the achievement of competencies and learning goals. Because by advancing the development of Human Resources (HR) and providing benefits for each country. Through understanding the background, we realize that formal learning resource centers must be able to adapt to changing times and technology to remain relevant. The research objectives brought a focus to understanding the basic concepts, goals, and role of formal learning resource centers. Overall, this research discusses the importance of a formal learning resource center as the main foundation in supporting learning in formal education institutions. Thus, a deep understanding of the basic concepts, objectives and role of formal learning resource centers is key in facing the dynamics of modern education. With this research, it is hoped that it can make a real contribution to the development of better educational policies and practices, as well as provide encouragement for further research in this area.